The Implementation of Multicultural- Based Sociology Learning in Senior High School - Rochana, Totok (Universitas Negeri Semarang, 2020)
This study examines the implementation ofÃ‚Â multicultural-based sociology learningÃ‚Â inÃ‚Â senior high school.Ã‚Â The objectives of this studyÃ‚Â are:Ã‚Â (1) To describe the sociology learning that is carried out currently;Ã‚Â and (2) to describe the implementation of multicultural-based sociology learning.Ã‚Â This studyÃ‚Â employed a qualitative approach to produce a description and analysis of findings.Ã‚Â The subjects of the study were sociology teachers in Kendal Regency.Ã‚Â The type of data collection was both in the form of quantitative data and qualitative data.Ã‚Â The data were collected using observation and interview guidelines.Ã‚Â DataÃ‚Â analysisÃ‚Â usedÃ‚Â descriptive qualitative analysis with interactive techniques.Ã‚Â The current implementation of sociology learning is based on the learning objectives of sociology, namely to develop sociology knowledgeÃ‚Â and practice to improve studentsÃ¢â‚¬â„¢ social skills.Ã‚Â Based on theÃ‚Â objectivesÃ‚Â of sociology learning, it influences theÃ‚Â learning approaches, models,Ã‚Â methods, media and resources, and assessment.Ã‚Â The implementation of multicultural-based sociology learning is based on the goal of multicultural learning. The learning is addressed asÃ‚Â an effort to developÃ‚Â students' abilityÃ‚Â Ã‚Â to viewÃ‚Â Ã‚Â Ã‚Â different cultures and toÃ‚Â be positive towards cultural, racial, and ethnic differences.Ã‚Â Based on these learning objectives, the implementation of sociology learning differs in termsÃ‚Â of learning approaches, models, methods, and assessments.